2020
DOI: 10.1093/toxres/tfaa032
|View full text |Cite
|
Sign up to set email alerts
|

D-Penicillamine prolongs survival and lessens copper-induced toxicity in Drosophila melanogaster

Abstract: D-penicillamine (DPA) is an amino-thiol that has been established as a copper chelating agent for the treatment of Wilson’s disease. DPA reacts with metals to form complexes and/or chelates. Here, we investigated the survival rate extension capacity and modulatory role of DPA on Cu2+-induced toxicity in Drosophila melanogaster. Adult Wild type (Harwich strain) flies were exposed to Cu2+ (1 mM) and/or DPA (50 μM) in the diet for 7 days. Additionally, flies were exposed to acute Cu2+ (10 mM) for 24 h, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Our results revealed that 25 DAMs were identified in both GM and GI groups. In the comparative analysis of GM and CK groups, it was observed that sev-eral DAMs that are critical for growth, reproduction, and detoxification metabolism were significantly reduced in the GM group, such as uridine, 5, 6-dihydroxyindole-2-carboxylic acid, and penicillamine [36][37][38]. These results indicated that the metabolic disorder of gypsy moth larvae in the GM treatment group occurred, consistent with the growth retardation of gypsy moth larvae mentioned above.…”
Section: Discussionsupporting
confidence: 55%
“…Our results revealed that 25 DAMs were identified in both GM and GI groups. In the comparative analysis of GM and CK groups, it was observed that sev-eral DAMs that are critical for growth, reproduction, and detoxification metabolism were significantly reduced in the GM group, such as uridine, 5, 6-dihydroxyindole-2-carboxylic acid, and penicillamine [36][37][38]. These results indicated that the metabolic disorder of gypsy moth larvae in the GM treatment group occurred, consistent with the growth retardation of gypsy moth larvae mentioned above.…”
Section: Discussionsupporting
confidence: 55%
“…The same GQD accumulation process might also occur in the presence of V 5+ and considerably enhance the fluorescence intensity of GQD. Regarding the fact that DPA has been considered as Cu 2+ chelator, 41‐43 the GQD‐DPA can be accumulated through N‐Cu 2+ ‐N and S − ‐Cu 2+ ‐S − interactions of copper ion‐DPA. Thus, in the presence of Cu 2+ , considering the chelating behavior of DPA toward Cu 2+ , an immediate and unstable color alternation occurred.…”
Section: Introductionmentioning
confidence: 99%